Nurses' knowledge and perceptions of and attitudes towards aspects of the new health systems framework: a qualitative case-study of the nurses employed at three public health facilities in the West District, City of Tygerberg, Cape Town - Marco, Colleen (Department of Paediatrics and Child Health, 2026)
A qualitative case study was conducted amongst nurses employed at the Elsies River's Community Health Centre, Community Health Clinic and Midwife Obstetric Unit. The purpose of the study was to gain insight into the nurses' knowledge and perceptions of and attitudes, towards key aspects of the new health systems framework, namely, the concept of Primary Health Care, the structure of the District Health System and selected aspects of the Maternal, Child and Women's Health Policy framework. An additional purpose was to gain insight into the nurses' Scope of Practice and whether nurses felt they were adequately skilled to provide a quality Primary Health Care service at district level. The first phase of the study involved individual interviews with nineteen nurses from the three main nursing categories. The second phase consisted of a focus group discussion in which five Registered Nurses participated. The study findings indicate that the nurses lack the knowledge and understanding of the key aspects of the new health systems framework. There has not been adequate consultation between the health authorities and the nurses, with respect to the formulation of the new health policy framework and the implementation thereof at local and district level. This resulted in negative attitudes being adopted by these nurses towards their superiors, the community and towards the new health systems framework. The nurses were found to not have adequate clinical skills to implement the new health policies. Furthermore, in-service training was identified as important, in order to render an effective Primary Health Care service. The training programs of these nurses were mainly curative-based and did not equip them to function competently within the Primary Health Care-based health service. Changes in the nursing education curriculum are discussed in order for a re-orientation towards Primary Health Care to occur. Specific recommendations are presented regarding the reorientation and training of nurses and appropriate methods to involve them in the development of the District Health System at local level.